A nurse-led conceptual model to inform patient-centred, type 2 diabetes mellitus management in public clinical settings. (December 2021) - Foluke Bosun-Arije, Stella; Chibuzor Nwakasi, Candidus; Ekpenyong, Mandu; Serrant, Laura; Esther Sunday-Abel, Temitope; Ling, Jonathan
Background: Globally, there is an increased need to provide patient-centred care for people diagnosed with type 2 diabetes mellitus. In Nigeria, a poorly financed health system has worsened the difficulties associated with managing type 2 diabetes mellitus in clinical settings, causing a detrimental effect on patient-centred care. Aims: We aimed to develop a conceptual model to promote patient-centred type 2 diabetes mellitus care in clinical settings. We explored nurses' contextual perceptions of clinical practices and operations in light of type 2 diabetes mellitus management across public hospitals in Lagos, Nigeria. Identifying a nurse-led intervention is critical to care optimisation for people diagnosed with type 2 diabetes mellitus. Methods: We adopted a qualitative approach. Using the constant comparison method and semi-structured questions and interviewed practice nurses, with over one year's experience and who were working in public hospitals across Lagos, Nigeria. The framework method was used to analyse the data obtained. Results: Nurses provided insight into four areas of patient-centred type 2 diabetes mellitus management in clinical settings: empowering collaboration; empowering flexibility; empowering approach; and empowering practice. Nurses discussed an empowering pathway through which health settings could provide patient-centred care to individuals diagnosed with type 2 diabetes mellitus. The pathway entailed the integration of macro, meso and micro levels for patient management. Nurses' accounts have informed the development of a conceptual model for the optimisation of patient care. Conclusions: The model developed from this research sits within the patient-centred care model of healthcare delivery. The research sits within the patient-centred care model of healthcare delivery. inform patient-centred care, not only in countries with poorly financed healthcare systems, but in developed countries with comparatively better healthcare.